Aplikasi Terintegrasi SIPONTREN dalam Meningkatkan Efisiensi Administrasi di Yayasan Nurul Amin - M . Syafiih; Nur Aisyah; Nadiyah Nadiyah; Nilna Widia Hastuti; Titimatul Qomariah; M. Ilham Zidni Syauqillah (GUYUB: Journal of Community Engagement, 2024)
This community service program aims to enhance data management efficiency at Yayasan Nurul Amin by implementing the Pangkalan Data Pesantren (PDTREN) application system using the Asset-Based Community Development (ABCD) approach. The main issue faced was the manual management of student, financial, and administrative data, leading to reporting delays and difficulties in monitoring. The goal of this service is to develop an information system that integrates and simplifies data management, and to improve technology skills within the foundation. The approach used is ABCD, which focuses on leveraging the assets and capabilities within the community, involving needs analysis, system design, in-person testing with 20 users, and training. The data collected includes system testing results, user feedback, and evaluation of training effectiveness. The conclusion of this program shows that the SIPONTREN system successfully improved data management efficiency, expedited reporting processes, and enhanced student monitoring. The training provided also significantly increased the technology skills of the foundation’s staff, supported system sustainability, and empowered the community. This program contributes significantly to the modernization of educational management in pesantren and can serve as a model for similar educational institutions